Sprache im Spannungsfeld zwischen Linguistik und Sprachlernforschung - Kelz, Heinrich P. (Glottodidactica, 2006)
Against a common question about the influence of linguistics on theories of foreign language teaching and learning in this article a contrary question concerining a reverse relation is asked: what is the influence of theory of foreign language teaching and learning on linguistics? It concerns esepcially contrastive analysis and factors determining the development of students’ interlanguage.